Molecular, cytogenetic, and clinical characterisation of six XX males including one prenatal diagnosis. Issue 9 (September 1998) - Margarit, E; Soler, A; Carrió, A; Oliva, R; Costa, D; Vendrell, T; Rosell, J; Ballesta, F
Abstract : Cytogenetic analysis, fluorescent in situ hybridisation (FISH), and molecular amplification have been used to characterise the transfer of Yp fragments to Xp22.3 in six XX males. PCR amplification of the genes SRY, RPS4Y, ZFY, AMELY, KALY, and DAZ and of several other markers along the Y chromosome short and long arms indicated the presence of two different breakpoints in the Y fragment. However, the clinical features were very similar in five of the cases, showing a male phenotype with small testes, testicular atrophy, and azoospermia. All these patients have normal intelligence and a stature within the normal male range. In the remaining case, the diagnosis was made prenatally in a fetus with male genitalia detected by ultrasound and a 46, XX karyotype in amniocytes and fetal blood. Molecular analysis of fetal DNA showed the presence of the SRY gene. FISH techniques also showed Y chromosomal DNA on Xp22.3 in metaphases of placental cells. To our knowledge, this is the second molecular prenatal diagnosis reported of an XX male.